La incidencia intertemporal de los impuestos sobre la distribución del ingreso en Argentina; The intertemporal incidence of taxes on income distribution in Argentina - Darío Rossignolo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– The aim of this paper is calculating the impact of taxes on inequality of lifetime income distribution in Argentina. Unlike other previous studies on the matter, which performed calculations on annual incidence or approximations on the measurement of lifetime income through current consumption expenditure, the approach to lifetime income measurement will be pursued through measuring income on the sources side. Compared to current income analysis, tax system turns out to be less regressive, given that the less progressivity of direct taxes which is more than compensated by the less regressivity of indirect taxes.
Keywords: H2; I3; D3; 330; taxes; lifetime income; inequality